Adapting the English Language Teaching Curriculum to Overcome Resource Limitations in Rural Areas - Nurteteng, Nurteteng; Sunra, La; Dollah, Syarifuddin (Universitas Negeri Gorontalo, 2024)
This research explores the adaptation of the English Language Teaching (ELT) curriculum to address the significant resource limitations faced in rural areas, specifically in Sorong, West Papua, Indonesia. The study aims to investigate how teachers creatively modify lesson plans, instructional methods, and assessment strategies in environments lacking essential resources, such as teaching materials, technological tools, and professional development opportunities and the impact on the students' outcomes. Using a qualitative multi-case study approach, data were gathered through semi-structured interviews, classroom observations, and document analysis over a two-month period. The findings reveal that teachers employed various strategies to cope with resource constraints, such as simplifying lesson content, utilizing locally available materials, and incorporating peer collaboration in the classroom. These adaptations resulted in enhanced student participation and improvements in oral communication skills. However, significant challenges were observed in fostering literacy, particularly reading and writing skills, due to the scarcity of instructional resources and limited teacher training. Moreover, while short-term engagement and speaking proficiency increased, the long-term impacts on overall English proficiency remained limited. The study underscores the need for comprehensive professional development for rural teachers and better access to teaching materials to fully bridge the educational gap between urban and rural students. Ultimately, these findings offer valuable insights for future curriculum development aimed at improving language education in resource-limited settings.